2015
DOI: 10.1097/jps.0000000000000050
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Administration for Postoperative Pain in Children With Developmental Delay

Abstract: Introduction: Parent-/nurse-controlled analgesia (PNCA) has been shown to be safe and effective for a variety of pediatric patient populations, yet no studies were found that assessed parent or nurse satisfaction with this opioid delivery system. The purpose of this study was to explore parent and nurse satisfaction and factors influencing satisfaction with three opioid delivery systems: PNCA with and without a basal infusion and intravenous, as needed (PRN) opioids for children with developmental delay.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Ultimately, we cannot know whether the low PNCA use by parents was related to the amount of time they were present or absent, the education they received, their preference for nurses to be entirely responsible for medication administration, or other causes. Coupled with results of our previous study (Czarnecki et al, 2015), these results call into 1.00 (0.00-2.44) 1.00 (0.00-2.55) 2.28 (1.80-e) COI POD 0 1.67 (0.00-4.42) 2.00 (0.00-3.63) 0.80 (0.00-5.00) POD 1 1.083 (0.00-3.18) 1.41 (0.00-3.67) 0.67 (0.00-3.54) POD 2 1.83 (0.58-3.42) 1.86 (0.70-3.79) 2.00 (0.00-3.071) POD 3…”
Section: Strengths and Limitationssupporting
confidence: 81%
See 3 more Smart Citations
“…Ultimately, we cannot know whether the low PNCA use by parents was related to the amount of time they were present or absent, the education they received, their preference for nurses to be entirely responsible for medication administration, or other causes. Coupled with results of our previous study (Czarnecki et al, 2015), these results call into 1.00 (0.00-2.44) 1.00 (0.00-2.55) 2.28 (1.80-e) COI POD 0 1.67 (0.00-4.42) 2.00 (0.00-3.63) 0.80 (0.00-5.00) POD 1 1.083 (0.00-3.18) 1.41 (0.00-3.67) 0.67 (0.00-3.54) POD 2 1.83 (0.58-3.42) 1.86 (0.70-3.79) 2.00 (0.00-3.071) POD 3…”
Section: Strengths and Limitationssupporting
confidence: 81%
“…Parents in both groups underwent a consenting and survey process that clearly conveyed our interest in their infant's pain experience, which in turn may have affected satisfaction ratings. As high parent satisfaction with pain management has been demonstrated in previous studies of various analgesic delivery systems (Choi et al, 2008;Czarnecki et al, 2015;Muthusamy et al, 2010;Twycross & Collis, 2013;Twycross & Finley, 2013), it is not known to what extent parents' awareness of our interest may have contributed to the high satisfaction found in our current study. However, this would not explain the between-group differences in parents' ratings of their satisfaction with their involvement in their infants' care.…”
Section: Strengths and Limitationsmentioning
confidence: 57%
See 2 more Smart Citations
“…21 Studies on the use of P/NCA have demonstrated decreased pain scores, lower opioid dosages, and improved staff and parent satisfaction. 20,22,23 Despite these advantages, many papers advise that P/NCA should be used only if vigilant monitoring and access to intensive care facilities are available due to the possibility of adverse or critical events. 20,24,25 The use of P/NCA in neonates has not been systematically reviewed; therefore, the safety and effectiveness of this method of analgesia for this population are not well established.…”
mentioning
confidence: 99%